MAX WEBER'S PERSPECTIVE CHARISMA: Analysis of the Religious Reality Concerning Abuya Amran Waly and the Majlis for the Study of Tauhid and Tasawwuf - Irwanto; Darmadi, Darmadi; Zainal, Suadi (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study aims to analyse the religious dynamics inside the Acehnese social context through the perspective of Max Weber's charisma theory. This study focuses on the phenomenon of Abuya Amran Waly and the Majelis Pengkajian Tauhid Tasawuf Indonesia (MPTT-I), which has generated discussion among the public and scholars in Aceh. In Weber's sociology of religion, charisma is considered a fundamental component in the development and transformation of religious authority. The employed methodology is a literature review employing a qualitative approach and content analysis. The analysis indicates that Abuya Amran Waly's allure, comprising both wahby (grace) and kasbi (effort), functioned as the principal factor in maintaining his prominence despite resistance and repudiation from the majority of dayah scholars. This charisma is further entrenched through the MPTT-I organisation. This research illustrates that understanding charisma as a social construct clarifies how the impact of religious leaders can transform into a communal movement, despite substantial theological and political resistance.